Daily Activity Budget Of Banded Langur (Presbytis Femoralis) In Malaysia - Mohd Faudzir, Najmuddin; Hidayah, Haris; Noratiqah, Norazlimi; Badrul Munir, Md Zain; Mohd Ridwan, Abdul Rahman; Rohani, Shahrool Annuar; Asiyahtul Husna, Hassan; Muhammad Abu Bakar, Abdul Latiff (Penerbit UMT, 2020)
Banded langur (Presbytis femoralis) is an endangered leaf-eating colobine, found in Johor and Pahang in Malaysia. However, with less than 500 individuals reported to be surviving in Johor, their behaviour and ecology remain unknown among primatologists. This study provides the first systematic data on the daily activity budget of the species in Malaysia. Scan sampling technique was used to observe and record P. femoralis behaviour with 10 min interval starting from February 2018 to November 2018. The results are based on 186 h and 20 min of direct observation in the wild. The animals spent most of the time for resting (43 ± 13%) followed by moving (26 ± 9%), feeding (26 ± 7%), social activities (4 ± 3%), and others (1 ± 0%). Seasonality significantly influences the activity budget of the animals resulting in increased resting and moving in the non-fruiting season. Feeding activities decreased in the non-fruiting season compared with the fruiting season, whereas social activities remained the same. We concluded that the daily activity budget of P. femoralis in this study portrays comparable behavior to other langurs in Malaysia that would help in conservation and management of the species in terms of understanding temporal and spatial requirements of P. femoralis in a highly fragmented habitat.